2024
DOI: 10.1007/s40121-024-00924-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on the Incidence of Herpes Zoster: A Narrative Literature Review

Raunak Parikh,
Mitra Yousefi,
Desmond Curran
et al.

Abstract: Coronavirus disease 2019 (COVID-19) has had a broad impact on health services and health outcomes. During the pandemic, there were numerous reports of herpes zoster (HZ) in people with COVID-19 and in COVID-19 vaccine recipients. The aim of this review is to elucidate the global effects of the COVID-19 pandemic on HZ. It is postulated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection produces an immunosuppressive state that favours varicella zoster virus (VZV) reactivation. Three larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Two large retrospective cohort studies have shown a small (14–15%) but significant increased risk of HZ after COVID-19 [ 30 , 31 ]. In addition, some but not all observational studies have reported an increased risk of HZ in general [ 32 34 ] and HZO in particular [ 35 38 ] after COVID-19 vaccination [ 39 , 40 ]. A large US healthcare claims database containing data from 1,959,157 patients who received at least one dose of a COVID-19 vaccine showed no increased risk of HZO after receipt of any COVID-19 vaccine [ 40 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Two large retrospective cohort studies have shown a small (14–15%) but significant increased risk of HZ after COVID-19 [ 30 , 31 ]. In addition, some but not all observational studies have reported an increased risk of HZ in general [ 32 34 ] and HZO in particular [ 35 38 ] after COVID-19 vaccination [ 39 , 40 ]. A large US healthcare claims database containing data from 1,959,157 patients who received at least one dose of a COVID-19 vaccine showed no increased risk of HZO after receipt of any COVID-19 vaccine [ 40 ].…”
Section: Risk Factorsmentioning
confidence: 99%